Effects of mobile application‐based instructional module of physical restraint among Intensive Care Unit nurses in Sharjah, United Arab Emirates - Kavumpurath, Janisha (2023)
Introduction: Traditional Continuing Nursing Education (CNE) faces challenges in scheduling and attendance, leading to the exploration of online alternatives, especially during the pandemic. Online CNE enhances convenience and accessibility, providing a platform to improve nursesʹ knowledge and skills, particularly busy nurses in Intensive Care Units (ICUs), where procedures like physical restraint (PR) techniques are crucial for patient safety. This study assesses the impact of a mobile application‐based instructional module on knowledge, attitude, and practice of PR among ICU nurses in Sharjah, United Arab Emirates. Methodology: In a quantitative experimental study with a randomized control trial, ICU nurses from four ministry hospitals in Sharjah participated after obtaining Ethical approvals. After developing a knowledge questionnaire, attitude scale, self‐reporting practice checklist, and the mobile application‐based instructional module, expert validation ensured tool quality, followed by a pilot study. The toolsʹ reliability was assessed using Cronbachʹs alpha. Sixty‐four participants were randomly selected, with 32 in the experimental group (EG) receiving the mobile application‐based educational program, while the remaining 32 comprised the Control group (CG) without the program. Results and Conclusion: The assessment tool exhibited good internal consistency (Cronbachʹs alpha: EG Knowledge=0.77, Attitude=0.69, Practice=0.77; CG Knowledge=0.76, Attitude=0.83, Practice=0.62). Significant correlations were found with the sociodemographic variables. In the EG, knowledge correlated with gender and prior PR education, and attitude correlated with previous education. In the CG, practice correlated with clinical experience. Knowledge levels were grouped into four tiers: advanced (>15), proficient (>12 to 15), basic (>8–12), and poor (≤8). The EG significantly improved median knowledge scores (8 to 14, p < 0.01, mean difference = 5.03). Conversely, the CG showed a nonsignificant change in knowledge scores (12.5 to 12, p = 0.08, mean difference = 0.70). Crucially, a significant pre‐ and post‐intervention knowledge score difference was observed between the EG and the CG (EG: 6, CG: 1, p < 0.01). Attitude categories included highly positive (>70), positive (>66 to 70), neutral (>61‐66), and negative (≤61). In the EG, mean scores significantly increased postintervention (68±7.72), up by 8.76±1.09 (p < 0.01). In the CG, pre‐ to post‐test change was minimal (67.9±5.18), with a non‐significant difference of 1.37±1.06 (p = 0.20). A significant difference in pre‐ and post‐intervention attitude scores was observed between the EG and the CG (EG: 9, CG: 4, p < 0.01). Self‐reported practice levels, proficient (>71), competent (>65 to 71), needing improvement (>60–65), and inadequate (≤60) exhibited a significant increase in the EG (from 59 to 72, p < 0.01, mean difference = 10.82). Conversely, the CG showed a nonsignificant change (from 63.5 to 63.5, p = 0.16, mean difference = 0.66). The observed difference in pre‐ and post‐intervention practice scores between the EG and CG was highly statistically significant (EG: 13, CG: 2.5, p < 0.01). The mobile application‐based education intervention significantly improved knowledge, attitude, and practice in PR for nurses. Integrating such education is crucial for promoting best practices and patient safety. Further research is needed to explore long‐term knowledge retention and broader impacts on clinical performance.